Nonmetropolitan sexual and gender minority youths' friendships: Perceptions of social support among SGM and non-SGM peers. Issue 4 (2nd October 2017) - Paceley, Megan S.; Hwu, Amanda; Arizpe, H. Denise
ABSTRACT: Sexual and gender minority (SGM) youth are at risk of victimization which can lead to poor outcomes. Social support can mitigate the effects of minority stressors, yet little is known about social support among nonmetropolitan SGM youth. This study utilized minority stress theory (Meyer, 2003) and Weeks' (1996) theory of how sexual minority communities are constructed to understand how nonmetropolitan SGM youth perceive the support they receive from SGM and non-SGM friends. Qualitative interviews were conducted with nonmetropolitan SGM youth. Youth received general emotional support, relationship advice, and protection from SGM and non-SGM friends. From their SGM friends, participants reported receiving greater closeness and emotional intimacy and assistance with SGM identity development. Participants indicated that receiving acceptance for their SGM identity was important from their non-SGM friends. Participants also discussed the limits to support their non-SGM friends could offer. Implications for practice and research are discussed.